The Solar Neutrino Problem Has Not Been Solved - Universe, Helical (JOURNAL OF ADVANCES IN PHYSICS, 2017)
A closer look at the data collected from different detectors, reveal that the so-called solar neutrino problem is far from being solved. And contrary to the assessment of the Nobel Committee, the experimental results from the Sudbury Neutrino Observatory cannot be a confirmation of the Standard Solar Model. In fact, the obsoleteness of the current model has been recently exposed by the crisis of solar abundance. Furthermore, using images obtained by the Solar Dynamics Observatory, researchers found the convective motions (the plasma motions at the Sun’s interior) to be nearly 100 times smaller than current theoretical expectations.